Simplify the expression:
2(3 + 4m) =
11 answers
2(3 + 4m) = 6 + 8m
Simplify the expression:
(4n − 5)(0.5) =
(4n − 5)(0.5) =
(4n - 5)(0.5) = 2n - 2.5
Simplify the expression:
–3.3(–5.5 + g) =
–3.3(–5.5 + g) =
–3.3(–5.5 + g) = 18.15 - 3.3g
Simplify the expression:
–4.5(–4.1 + 0.7b) =
–4.5(–4.1 + 0.7b) =
–4.5(–4.1 + 0.7b) = 18.45 - 3.15b
Solve for w.
2.8 + 2w = 8.8
w =
2.8 + 2w = 8.8
w =
To solve for w, we need to isolate w on one side of the equation.
2.8 + 2w = 8.8
Subtract 2.8 from both sides:
2w = 8.8 - 2.8
2w = 6
Divide both sides by 2:
w = 6/2
w = 3
Therefore, w = 3.
2.8 + 2w = 8.8
Subtract 2.8 from both sides:
2w = 8.8 - 2.8
2w = 6
Divide both sides by 2:
w = 6/2
w = 3
Therefore, w = 3.
Solve for r.
r
2
− 1.1
= 1.1
r =
r
2
− 1.1
= 1.1
r =
To solve for r, we need to isolate r on one side of the equation.
{{{r/2 - 1.1 = 1.1}}}
First, add 1.1 to both sides:
{{{r/2 = 2.2}}}
Next, multiply both sides by 2 to cancel out the division:
{{{r = 2.2*2}}}
Simplifying:
{{{r = 4.4}}}
Therefore, r = 4.4.
{{{r/2 - 1.1 = 1.1}}}
First, add 1.1 to both sides:
{{{r/2 = 2.2}}}
Next, multiply both sides by 2 to cancel out the division:
{{{r = 2.2*2}}}
Simplifying:
{{{r = 4.4}}}
Therefore, r = 4.4.